Playing for keeps: a psychological measure of the probability of retaining a free agent in professional basketball - Lewis, Melanie (My University, 2018)
Existing research has provided insights into what drives individuals to voluntarily leave a job and join a different organization. This framework for understanding voluntary turnover has never been tested in the context of professional sports. Furthermore, the inability to retain talent has a negative financial impact on these organizations and has been shown to reduce team performance. Study one focuses on using archival data and the wisdom of the crowd to assess professional basketball players’ levels of job satisfaction, job embeddedness and leader-member exchange. Study two focuses on historic data directly provided by these athletes via post-game interview videos and public social media activity to assess the same psychological attributes. Results suggest that these three concepts successfully discriminate between which players choose to stay or leave. Comparisons of the different measurement approaches and relative predictive power provided by each attribute are also discussed. Keywords: Voluntary Turnover, Free Agency, Professional Sports
Keywords: Psychology; Sports; Psychometrics